Is It Human? Discriminating between Real Tracks and Track-Like Structures. Issue 1 (2nd January 2018) - Panarello, Adolfo; Santello, Lisa; Belvedere, Matteo; Mietto, Paolo
ABSTRACT: Some human footprints-like hollows in the tuffaceous ground of an ancient quarry and of a recent anthropic path, created by the inhabitants no more than 30 years ago near the small village of Carangi (Caserta province, Southern Italy), allowed scientists to study some of the most misleading alteration processes of the volcanic tuff formations. The closeness of this site to the "Ciampate del Diavolo" ichnosite, bearing some of the oldest human fossil footprints, and the common stratigraphical and sedimentological background permitted accurate comparisons between actual human fossil footprints and footprint-like depressions, which can be easily mistaken for actual fossil evidence. This comparative study has permitted the reporting of some useful features and advice on distinguishing actual fossil footprints from natural and/or anthropic pseudo-tracks.